Antimicrobial effect of different calcium silicate - Based bioceramic endodontic sealers against Enterococcus faecalis: An in vitro study - Salah M Abduljabbar; Ammar Abumostafa (Wolters Kluwer Medknow Publications, 2021)
Introduction: A successful root canal treatment ensures complete sealing of the root canal to abstain from re-infections. The efficiency of antimicrobial activity of the sealers is important for achieving long term success in root canal therapy. Aim: This study compared the antibacterial properties of three calcium silicate-based root canal sealers against Enterococcus faecalis at varying incubation time periods. Materials and Methods: This in vitro cross sectional experimental study was designed with three root canal sealers, namely, Endosequence/BC Sealer, CeraSeal, and BioRoot RCS. Freshly mixed selars were placed in agar plates infused with Enterococcus faecalis. Incubation at 37°C under anaerobic conditions was done for 1 week, during which measurements of the inhibition zones were recorded at 24 h, 48 h, 72 h, and 7 days. Data were compared using ANOVA, and Tukey's tests (P < 0.05). Results and Discussion: Bacterial growth inhibition was demonstrated by all the sealers tested, with antimicrobial activity being highest for BioRoot RCS and least for CeraSeal. An increase in duration of incubation, positively affected the antimicrobial properties. Conclusion: Significant difference (P < 0.05) of bacterial inhibition was observed among different time duration of 24 h compared to 48 h, 72 h, and 7 days, for all tested materials. Moreover, BioRoot RCS showed significant bacterial inhibition to tested microorganism.